“Then the Woman Left Her Water Jar”: Engaging Marginality and the Invisibilised Samaritan Woman in John 4:1–42 from an Asian Immigrant Perspective - Wong, Edward (Horizons in biblical theology, 2025)
First-generation Asian immigrants in the “West” often encounter persistent stereotypes of “perpetual foreigners” and “model minority” despite their societal contributions and integration efforts. Compared to native-born Asians, these new immigrants are frequently further marginalised as “Fresh off the Boat (FOB s),” a term describing their perceived dissonance from mainstream culture and their presumed need to conform to the dominant hegemony. This article explores the intercontextual overlaps between the marginalised and invisibilised experiences of Asian immigrants with John 4’s portrayal of the Samaritan woman. I examine how the text appropriates the Samaritan woman’s marginalised position to highlight both her need and the superiority of a saviour, Christ. I illustrate that the evangelist casts the woman as a perpetual foreigner by invisibilising her contribution to missions and silencing her voice among her fellow Samaritans within the Johannine story-world in a manner comparable to first-generation Asian immigrant experiences and the complex intra-Asian community dynamics.